2020
DOI: 10.2147/cmar.s240577
|View full text |Cite
|
Sign up to set email alerts
|

<p>TOP2A Promotes Cell Migration, Invasion and Epithelial–Mesenchymal Transition in Cervical Cancer via Activating the PI3K/AKT Signaling</p>

Abstract: Background/Objective: Topoisomerases type IIA (TOP2A) was identified to present with a high-expression pattern in cervical cancer. However, TOP2A role in the progression of cervical cancer remains unknown. Here, we aimed to explore the effect and reveal the underlying mechanism of TOP2A in the migration, invasion and epithelial-mesenchymal transition (EMT) of cervical cancer. Materials and Methods: The expression profiles of TOP2A in 20 paired cervical cancer tissues and the paracancerous normal tissues were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…Most importantly, over expression of IFIT1 or IFIT3 increased EGFR and AKT expression, which is closely related to the activation of the PI3K pathway (75). TOP2A can also activate the PI3K/AKT signaling pathway leading to cell migration (76), whereas an increased expression of KIF11 inhibited the activation of PI3K/AKT signaling pathway (77). In summary, the potential biomarker genes proposed for SLE diagnosis are closely related to PI3K pathway, and the use of PI3K inhibitors reversed the changes associated with ISG15, OAS1, OASL, and IFIT1 (72,78,79).…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, over expression of IFIT1 or IFIT3 increased EGFR and AKT expression, which is closely related to the activation of the PI3K pathway (75). TOP2A can also activate the PI3K/AKT signaling pathway leading to cell migration (76), whereas an increased expression of KIF11 inhibited the activation of PI3K/AKT signaling pathway (77). In summary, the potential biomarker genes proposed for SLE diagnosis are closely related to PI3K pathway, and the use of PI3K inhibitors reversed the changes associated with ISG15, OAS1, OASL, and IFIT1 (72,78,79).…”
Section: Discussionmentioning
confidence: 99%
“…All four genes showed significantly higher expression in CIN3 as compared to normal biopsies in the current study. Specifically, TOP2A, a promoter of epithelial-mesenchymal transition (EMT), has been associated with increased invasive properties of cancer cells, and has been suggested as a prognostic factor for cervical cancer [ 44 ]. Furthermore, TOP2A combined with CDKN2A mRNA expression showed high sensitivity and specificity for HSIL [ 45 ] in LBC samples.…”
Section: Discussionmentioning
confidence: 99%
“…Several of these regulators are responsible for genomic integrity. TOP2A, PTTG1 and SMC4 play central roles in chromosome stability and ERCC6 takes part in excision repair, of which dysregulation drives deleterious chromosomal aberrations and thus carcinogenesis [ 39 , 40 , 41 , 42 ]. Moreover, it has been reported that regulation of mRNA stability can govern cancer metastasis [ 43 ].…”
Section: Discussionmentioning
confidence: 99%